2023
DOI: 10.48550/arxiv.2303.03227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel Hybrid Networks: an interplay between quantum and classical neural networks

Abstract: Quantum neural networks represent a new machine learning paradigm that has recently attracted much attention due to its potential promise. Under certain conditions, these models approximate the distribution of their dataset with a truncated Fourier series. The trigonometric nature of this fit could result in angle-embedded quantum neural networks struggling to fit the non-harmonic features in a given dataset. Moreover, the interpretability of neural networks remains a challenge. In this work, we introduce a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As discussed in [15], all quantum neural networks that use angle embedding 5 as their encoding strategy produces a truncated Fourier series approximation to the dataset. Schuld et al [15] also specifically explored two families of architectures of quantum neurons: a single-qubit architecture with a series of sequential SU (2) gates and a multi-qubit architecture with parallel SU(2) encoding gates.…”
Section: Background Review-linear Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in [15], all quantum neural networks that use angle embedding 5 as their encoding strategy produces a truncated Fourier series approximation to the dataset. Schuld et al [15] also specifically explored two families of architectures of quantum neurons: a single-qubit architecture with a series of sequential SU (2) gates and a multi-qubit architecture with parallel SU(2) encoding gates.…”
Section: Background Review-linear Architecturesmentioning
confidence: 99%
“…It was argued [3] that such quantum neural networks (QNN) could have higher trainability, capacity, and generalization bound than their classical counterparts. Practically, hybrid quantum neural networks (HQNN) have shown promise in small-scale benchmarking tasks [4][5][6][7] and larger-scale industrial tasks [8][9][10]. Nevertheless, the utility, practicality, and scalability of pure QNNs are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have also shown that the prediction of heart failure as the cause of death can be effectively and more precisely predicted with the help of quantum machine learning algorithms instead of classical ones. Among many existing quantum methods, quantum neural networks [27][28][29][30][31][32] are one of the most promising. For instance, in [33], the authors use a quantum generative adversarial neural network (GAN) with a hybrid generator to discover new drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Unlike their classical counterparts, QNNs are able to learn a generalized model of a dataset from a substantially smaller training set [15][16][17] and typically have the potential to do so with polynomially or exponentially simpler models. [18][19][20] Thus, they provide a promising opportunity to subvert the scaling problem encountered in classical machine learning, [5,[21][22][23][24][25][26][27] which presents a serious challenge for data-intensive problems that are increasingly bottle-necked by hardware limitations. [28][29][30] Nonetheless, even for a small dataset, training QNNs requires on the order of a million circuit evaluations.…”
Section: Introductionmentioning
confidence: 99%